2021
DOI: 10.1007/s00223-021-00833-4
|View full text |Cite
|
Sign up to set email alerts
|

RTEF-1 Inhibits Vascular Smooth Muscle Cell Calcification through Regulating Wnt/β-Catenin Signaling Pathway

Abstract: Vascular calcification (VC) is highly prevailing in cardiovascular disease, diabetes mellitus, and chronic kidney disease and, when present, is associated with cardiovascular events and mortality. The osteogenic differentiation of vascular smooth muscle cells (VSMCs) is regarded as the foundation for mediating VC. Related transcriptional enhancer factor (RTEF-1), also named as transcriptional enhanced associate domain (TEAD) 4 or transcriptional enhancer factor-3 (TEF-3), is a nuclear transcriptional factor wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Wnt/β-cate-nin signaling could play a crucial role in the regulation of high phosphate-induced calcification of VSMCs via the induction of osteogenic genes such as Runx2 ( 15 ). The present study and other reports ( 27 , 28 ) demonstrated that high phosphate induces two active forms of β-catenin, β-catenin dephosphorylated at Ser37/Thr41 via the inactivation of GSK-3β through Ser9-phosphorylation and β-catenin phosphorylated at Ser675, resulting in promotion its stability and transcriptional activity. These changes were completely reversed by treatment with NMB siRNA or PD168368 ( Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Wnt/β-cate-nin signaling could play a crucial role in the regulation of high phosphate-induced calcification of VSMCs via the induction of osteogenic genes such as Runx2 ( 15 ). The present study and other reports ( 27 , 28 ) demonstrated that high phosphate induces two active forms of β-catenin, β-catenin dephosphorylated at Ser37/Thr41 via the inactivation of GSK-3β through Ser9-phosphorylation and β-catenin phosphorylated at Ser675, resulting in promotion its stability and transcriptional activity. These changes were completely reversed by treatment with NMB siRNA or PD168368 ( Fig.…”
Section: Discussionsupporting
confidence: 80%
“…To further verify the effect of hsa_circRNA_0008028 on cell calcification and osteogenic differentiation, HG-treated VSMCs were coincubated with 10 mmol/L β -glycerophosphate ( β -GP) for 12 days after transfection [ 21 ]. As expected, obvious calcification, characterized by increased alkaline phosphatase (ALP) activity ( Figure 2(e) ) can be observed in cells in the HG group and the HG and si-NC group.…”
Section: Resultsmentioning
confidence: 99%
“…Before the subsequent experiments, all cells were kept quiescent by starvation for 24 hours and then treated with 5.5 mmol/L D-glucose (normal glucose (NG)) or 30 mmol/L D-glucose (HG) for 48 hours. All VSMCs to be tested for calcification and osteogenic differentiation were treated with HG and coincubated with 10 mmol/L β -glycerophosphate ( β -GP, Sigma-Aldrich, USA) for 12 days after siRNA transfection or overexpression [ 21 ]. VSMCs exposed to 30 mmol/L mannitol (MA, Aladdin, China) was chosen as the negative control.…”
Section: Methodsmentioning
confidence: 99%
“…The transcription factor XBP1, synergistically with Runx2, is involved in VC due to oxidative stress ( Liberman et al, 2011 ). TEAD4 is a nuclear transcription factor that inhibits vascular calcification by regulating the Wnt/β-Catenin signaling pathway ( Cong et al, 2021 ). By intervening in VC hub genes, it may be a new direction for individualized genomic therapy of VC.…”
Section: Discussionmentioning
confidence: 99%